2016
DOI: 10.1371/journal.pone.0162192
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Predicts the Risk for Future Type 2 Diabetes

Abstract: Recently, 5 amino acids were identified and verified as important metabolites highly associated with type 2 diabetes (T2D) development. This report aims to assess the association of tryptophan with the development of T2D and to evaluate its performance with existing amino acid markers. A total of 213 participants selected from a ten-year longitudinal Shanghai Diabetes Study (SHDS) were examined in two ways: 1) 51 subjects who developed diabetes and 162 individuals who remained metabolically healthy in 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 50 publications
6
79
0
4
Order By: Relevance
“…Aromatic amino acids have been linked to insulin resistance (Chen et al, 2016; Wang et al, 2011a) and showed multiple pathway-specific changes (Figure 5B). Tryptophan levels in the cecum were decreased by metronidazole in all strains and by vancomycin in 129T mice, indicating the role of gut microbiota in tryptophan metabolism; however, this was not reflected by changes in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic amino acids have been linked to insulin resistance (Chen et al, 2016; Wang et al, 2011a) and showed multiple pathway-specific changes (Figure 5B). Tryptophan levels in the cecum were decreased by metronidazole in all strains and by vancomycin in 129T mice, indicating the role of gut microbiota in tryptophan metabolism; however, this was not reflected by changes in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…After 0.5, 4 and 16 hours, samples were collected to perform extraction of metabolites. Amino acids were measured in cell samples that were previously stored at −80°C using a quantitative UPLC-MS/MS platform (ACQUITY UPLC-Xevo TQ-S, Waters Corp., Milford, MA, USA) according to previously published methods (Chen et al, 2016a;Chen et al, 2016b). All chromatographic separations were performed with an ACQUITY BEH C18 column VanGuard pre-column (2.1×5 mm) and analytical column (2.1×100 mm).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Recent studies using metabolomics profiling have revealed serum levels of branched-chain and aromatic amino acids, including leucine, isoleucine, valine, phenylalanine, and tyrosine, are closely associated with the risk of future diabetes [11, 12]. However, metabolic alterations in diabetic atherosclerosis have not been reported.…”
Section: Introductionmentioning
confidence: 99%